PENGARUH PEMBERIAN INHALASI LEMON TERHADAP PENGURANGAN MUAL MUNTAH PADA IBU HAMIL TRIMESTER I DI PMB LESTARI CILEUNGSI KABUPATEN BOGOR TAHUN 2019 - Nurulicha Nurulicha (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Management of nausea and vomiting in pregnancy consists of non-pharmacological pharmacology, and complications. Non-pharmacological therapy is a type of complementary nursing therapy that can be used as an intervention to treat nausea including lemon aromatherapy. The purpose of this study is to prove the effect of lemon aromatherapy inhalation on the reduction of nausea and vomiting in first trimester pregnant women in PMB Lestari in 2019. This quantitative study uses an approach pre experimental one group pre test and post test. The study population was the total number of trimester I pregnant women who experienced nausea and vomiting by 22 people. The sampling technique of this research was purposive sampling. Statistical tests using the Wilcoxon Test. The results of the analysis showed that there was no increase in nausea and vomiting (0b), and persistent nausea and vomiting did not exist (0c). The conclusion of the study is a decrease and there is an effect after inhalation of lemon aromatherapy on nausea and vomiting in first trimester pregnant women. Suggestions in the study are expected that health workers can provide lemon aromatherapy inhalation as a complementary care for first trimester pregnant women who experience nausea and vomiting.